A Cinderella story - Wasserman, Robin; Dunlap, Leigh (New York : Scholastic, 2004)
Samantha, a high schooler whose life mirrors Cinderella's, defies her stepmother to attend the Halloween costume ball where she is supposed to finally learn the identity of her online love, Nomad, but she is shocked to find he is the most popular boy in school, and before she can unmask herself, she is forced to flee, leaving her cell phone behind.
"Based on the hit movie starring Hilary Duff!"--Cover.
4.9
3-6
Keywords: Orphans -- Fiction; Teenagers -- Fiction; Stepmothers -- Fiction; Man-woman relationships -- Fiction; Orphans -- Fiction; Teenagers -- Fiction; Stepmothers -- Fiction; Man-woman relationship -- Fiction